2021
DOI: 10.1371/journal.ppat.1009577
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic regulation of human T-cell leukemia virus by chromatin-insulator CTCF

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) is a retrovirus that causes an aggressive T-cell malignancy and a variety of inflammatory conditions. The integrated provirus includes a single binding site for the epigenomic insulator, CCCTC-binding protein (CTCF), but its function remains unclear. In the current study, a mutant virus was examined that eliminates the CTCF-binding site. The mutation did not disrupt the kinetics and levels of virus gene expression, or establishment of or reactivation from latency. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…The viral CTCF-BS (vCTCF-BS) is located at a sharp border in epigenetic modifications within the pX region of the proviral genome (Satou et al, 2016). The presence of the vCTCF-BS disrupts host chromatin structure and looping, regulates viral mRNA splicing, and maintains/regulates the epigenetic barrier found in the pX region (Melamed et al, 2018;Cheng et al, 2021). However, loss of the vCTCF-BS did not disrupt the ability of the virus to immortalize target cells in vitro or establish persistence in a rabbit model of infection (Martinez et al, 2019).…”
Section: Antisense Transcription In Human T-cell Leukemia Virusesmentioning
confidence: 98%
“…The viral CTCF-BS (vCTCF-BS) is located at a sharp border in epigenetic modifications within the pX region of the proviral genome (Satou et al, 2016). The presence of the vCTCF-BS disrupts host chromatin structure and looping, regulates viral mRNA splicing, and maintains/regulates the epigenetic barrier found in the pX region (Melamed et al, 2018;Cheng et al, 2021). However, loss of the vCTCF-BS did not disrupt the ability of the virus to immortalize target cells in vitro or establish persistence in a rabbit model of infection (Martinez et al, 2019).…”
Section: Antisense Transcription In Human T-cell Leukemia Virusesmentioning
confidence: 98%
“…CTCF-binding sequences on the provirus suggest a new relationship between the provirus and host epigenome [ 23 ]. Some studies have shown that HTLV-1 disrupts the host chromatin structure by forming a loop between the provirus and the host genome, and the loop depends on the critical chromatin architectural protein CTCF [ 23 , 24 , 25 , 26 ]. Although it remains unclear how these changes contribute to the characteristics of infected cells, clonal structure, and pathogenesis of ATL, the impact of such insertional mutagenesis on the host epigenome is an essential insight into the pathogenicity of HTLV-1.…”
Section: Early Formation Of Epigenomic Abnormalities In Infected Cell...mentioning
confidence: 99%
“…In HTLV-1 infected cell lines and primary malignant cells from ATL patients, the 5′LTR (as L.545), but not the 3′ LTR, of provirus are highly methylated (117, 118). Recently, a suppressive regulation of HTLV-1 gene expression by CTCF was also reported (119,120). However, the mechanism of why all HTLV-1-infected cells uniformly switch to full transcriptional latency within a certain period is not known.…”
Section: Regulation Of Viral Gene Expression During Latent Infectionmentioning
confidence: 99%